Material Hibrid Komposit Nilon-Rami-Epoksi Untuk Roda Lori Inspeksi (Politeknik Perkeretaapian Indonesia Madiun, 2023)
Inspection lorry very important role in the maintenance of railway infrastructure. Technological modifications in the development of inspection lorry at the Madiun Indonesian Railways Polytechnic are continuing. Development of inspection lorry wheels using composite materials using nylon fiber and hemp fiber as reinforcement and epoxy resin as the matrix. This research was conducted to reduce the load of the third generation inspection lorry which initially used wheels made of nodular cast iron. In designing the wheels of inspection lorry made from composites, this must be taken into account properly so that they do not drop or skid while walking and comply with the main requirements for lorry that are easy to lift and move. The method of making inspection lorry wheels made of composites uses the hand lay-up method. The initial steps taken in this study were designing, determining materials and conducting functional tests. Testing the mechanical properties of the lorry wheel composite materials by diametral tensile strength test with ASTM D695 standard specimens. From the results of the diametral tensile strength test conducted, it was obtained that the specimen had the highest diametral tensile strength value, namely sample 1B of 76.88 MPa and the lowest strength was sample 2B with a tensile strength of 22.73 MPa. The diametral tensile strength value is influenced by the volume of reinforcing fibers, the volume of the binding matrix and the press mold load given to the molding of the composite. Function tests on straight tracks, points, level crossings and curved tracks can run smoothly without any derailments occurring. Noise test wheels made of composites have a lower noise level compared to lorry wheels using nodular cast iron